The First WTO's Ruling on National Security Exception: Balancing Interests or Opening Pandora's Box?. Issue 1 (January 2020) - Boklan, Daria; Bahri, Amrita
Abstract: For a multilateral system to be sustainable, it is important to have several escape clauses which can allow countries to protect their national security concerns. However, when these escape windows are too wide or ambiguous, defining their ambit and scope becomes challenging yet crucial to ensure that they are not open to misuse. The recent Panel Ruling in Russia – Measures Concerning Traffic in Transit is the very first attempt by the WTO to clarify the scope and ambit of National Security Exception. In this paper, we argue that the Panel has employed a combination of an objective and a subjective approach to interpret this exception. This hybrid approach to interpret GATT Article XXI (b) provides a systemic balance between the sovereign rights of the members to invoke the security exception and their right to free and open trade. But has this Ruling opened Pandora's box? In this paper, we address this issue by providing an in-depth analysis of the Panel's decision.